Trends in Labor Force Transitions of Older Men and Women - Peracchi, Franco; Welch, Finis (Journal of Labor Economics, 1994)
We use the Current Population Survey to describe what we believe are the most salient aspects of labor force behavior of older men and women during the last 2 decades. First, we show that early retirement has increased dramatically, and this trend continued through the 1980s. Second, we show that the factors that most sharply distinguish propensities toward early retirement are those usually associated with low wages. Third, we show that trends in reduced participation for older men parallel those for younger men, while a pattern of increasing female participation is to be expected given the behavior of younger cohorts.